Dewetting Model Study on a Spinning Substrate - Challenges for Low Chemical Consumption. (11th September 2015) - Sano, Ken-ichi; Mui, David; Kawaguchi, Mark
Abstract : A model is proposed to describe the wetting and dewetting dynamics on a spinning wafer with a non-wetting surface. The model is based on the dynamic balance between the wetting and dewetting velocities. The proposed model predicts a theoretical lower limit for the media flow rate to completely wet a wafer surface as a function of the contact angle and wafer rotational speed. The model predictions are found to agree reasonably well with experimental results. The model is also used to develop a low flow process for the removal of titanium nitride. A 66% flow rate reduction is achieved in comparison with the baseline process.